Characteristics of Biocellulose-Based Edible Film from Sago Wastewater (Metroxylon sago ROTTB.) on Various Glycerol Concentration - Yanti, Nur Arfa; Ahmad, Sitti Wirdhana; Ramadhan, La Ode Ahmad Nur; Ardiansyah, Ardiansyah; Indrawati, Indrawati (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2024)
This study aimed to investigate the the characteristics of biocellulose-based edible films from sago wastewater (Metroxylon sago ROTTB.) by incorporating varying concentrations of glycerol as a plasticizer. The edible films were made through a casting method using biocellulose from sago wastewater as the main ingredient. The treatments included the addition of varying glycerol concentrations to the edible films, namely 0.5, 1, and 1.5% (v/v), with three replications. The observed characteristics included physical (thickness, solubility, and moisture content of the film), mechanical (tensile strength, elongation percentage, and Young’s modulus/modulus of elasticity) with a universal testing machine, chemical structure using FT-IR, and surface morphological characteristics through scanning electron microscopy (SEM). The results showed that increasing the glycerol concentration in the edible films improved the physical characteristics including thickness, solubility, and moisture. However, there was a decrease in the mechanical characteristics, namely tensile strength, elongation percentage, and Young’s modulus of the film. The main components of edible films found were cellulose polymers, as indicated by characteristic functional groups, such as free-OH groups, aliphatic C-H, C-O, and β-1,4-glycosidic bonds. The surface morphology of the biocellulose edible film without glycerol was smoother compared to those containing glycerol. Biocellulose-based edible films from sago wastewater with glycerol concentrations of 0.5% and 1% showed physical-mechanical characteristics that fulfilled the Japanese Industrial Standard (JSI), indicating the potential for application as food packaging. These results indicated that incorporation of glycerol has an effect on the characteristics of the biocellulose-based edible films from sago wastewater.